Kinship Relation of Malvaceae Species Based on Morphological Characteristics - Marisa Agustina; Djufri Djufri; Cut Nurmaliah (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2019)
This study aimed to determine the kinship relationship of Malvaceae species based on morphological characteristics, this study uses a descriptive method that interprets the kinship of the species Malvaceae based on morphological characteristics. The object of the research is the species of Malvaceae namely hibiscus (Hibiscus archeri), waru (Hibiscus tiliaceus), rosella (Hibiscus sabdariffa), pulutan (Urena lobata L.), ocra (Abelmoschus esculentus), cotton (Gossypium hirsutum), sidaguri (Sida rhombifolia L.), kembang tidur (Malvaviscus penduliflorus), lanterns (Abutilon pictum). The parameters used are stem organs, leaves, and flowers. Data analysis was performed by calculating the Similarity Index (IS) and Dissimilarity Index (ID), the data in Cluster Analysis to group Malvaceae species based on the same number of characters. The results of the research show that the closest kinship relation owned by a combination of plants that has the lowest Dissimilarity Index (ID) value in the species of hibiscus (Hibiscus archeri) and kembang tidur (Malvaviscus penduliflorus). The conclusion of this study is there are three categories of relationships of the Malvaceae species, which are the closest kinship relation, close kinship relation, and the kinship relation are not close. The kinship relationship is remarkably close to the lowest Dissimilarity (ID) Index value indicated by the combination of hibiscus (Hibiscus archeri) and kembang tidur (Malvaviscus penduliflorus) with ID value = 25.